I La Galigo Folklore Illustration on Textile Media - Yosepin Sri Ningsih; John Martono; Zaini Rais (ITB Journal Publisher, LPPM ITB, 2014)
This project was an effort in conserving the I La Galigo epic story while at the same time adding value to silk, the famous textile product from South Sulawesi and the origin of I La Galigo. As a work of literature, I La Galigo is categorized as an epic. It is known locally as Sureq Galigo in Bugis. It is divided in a number of episodes or tereng. The most well-known tereng is the one which describes the relationship between Sawerigading and a princess called I We Cudai. From that relationship I La Galigo, the central character of this epic is born. For this project six of the most well-known episodes were selected because of the amount of available supporting data, both theoretical and visual. The selected episodes were translated from their original narrative form into visual language or images. The illustration technique used in this project was STP (Space Time Plane). With this technique every object is drawn from varying viewpoints in one frame, both in space and time. Hand embroidery was added to the painted images. The silk painting can be used as an interior element with value added by the I La Galigo illustrations. Keywords: I La Galigo; epic; Sulawesi; illustration; silk painting; space time plane.